Neutrosophic Semi βF-Contra Continuity in a Neutrosophic Topological Space (Contemporary Mathematics, 2024)
The main intention of this article is to propose the theory of a neutrosophic SβF contra continuous function, neutrosophic strongly SβF continuous function, neutrosophic strongly SβF contra continuous function and neutrosophic SβF contra irresolute function in neutrosophic topological spaces. Further several properties based on the above concepts have been studied. Many theorems based on the above ideas have been proved with the suitable illustration. Further the relationship connecting neutrosophic SβF contra continuous function, neutrosophic strongly SβF continuous function, neutrosophic strongly SβF contra continuous function and neutrosophic SβF contra irresolute function are studied and illustrated. Moreover, various theorems based on compositions of functions have been proved. In addition to this, the product of two neutrosophic sets is defined and related theorems have been proved.
Keywords: neutrosophic topology; neutrosophic SβF closed set; neutrosophic SβF-continuity; SβF-continuity; neutrosophic SβF-contra continuity; neutrosophic strongly SβF-continuity contra continuity and neutrosophic SβF-contra irresolute